Investors' Time Horizon and the Inefficiency of Capital Markets - Mayshar, Joram (Quarterly Journal of Economics, 1978)
I. Introduction, 187.—II. The monopoly problem 189.—III. Monopolistic value maximization, 195.—IV. Some remarks on financial uncertainty, 202.—V. Conclusion, 204.